Analisis Penilaian Kinerja Dan Kepuasan Kerja Yang Dimediasi Oleh Pengembangan Karier Dan Kompensasi (Studi pada Karyawan Bank BJB se-Kantor Wilayah Regional IV Banten) - Ramano, Angga; Prahiawan, Wawan; Ramdansyah, Agus David (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2021)
This study aims to examine the effect of performance appraisal on job satisfaction through career development and compensation as intervening variables. The study was conducted on 91 permanent employees of Bank BJB who worked in Regional Offices of Banten IV and had worked for at least 3 years using purposive sampling technique. Data analysis using SEM-PLS method. The results showed 1) Performance appraisal has a positive and significant effect on job satisfaction, where the better the performance appraisal, the higher the employee job satisfaction, 2) Performance appraisal has a positive and significant effect on career development, where the better the performance appraisal, the more Employee career development, 3) Performance appraisal has a positive and significant effect on compensation, where the better the performance appraisal, the higher the employee compensation, 4) Career development has no effect on job satisfaction, 5) Compensation has a positive and significant effect on satisfaction employee work, where the higher the compensation, the higher the job satisfaction.